Effect of Vimala Massage on Physiological Jaundice in Infants: A Randomized Controlled Trial - Seyyedrasooli, Alehe (Tabriz University of Medical Sciences, 2014)
Introduction: Considering the prevalence of Jaundice in newborn infants and the risk of developing acute Bilirubin encephalopathy, in early weeks after birth. the importance of Infancy, as well as positive effects of giving massage on physical and behavioral growth and evolution of infants, the current study has been aimed to investigate the effects of Vimala massage on neonatal physiological Jaundice. Methods: This is a single blind clinical trial study, 43 healthy term infants, with 1(st) day Bilirubin levels of less than 5mg/dl, carried out in Tabriz Al-Zahra hospital. Newborns were selected through convenience sampling and then randomly assigned to intervention and control groups. Control group received routine care, while newborns of intervention group received four days of Vimala massage starting from the first day of their birth. Main variables of study include transcutaneous Bilirubin and frequency of defecation. Collected data were analyzed by SPSS Ver.13 through Chi-square and Mann-Whitney tests. Results: There were no statistical significant differences between two groups for skin bilirubin, however the number of defecations in the intervention group exceeded than of control group, and was statistically significant. Conclusion: The Results show that Vimala massage within four days has no effect on increasing process of bilirubin, yet can affect the incidence rate of physiological Jaundice and care of infants by increasing defecation frequency.